TiP2O7 and Expanded Graphite Nanocomposite as Anode Material for Aqueous Lithium-Ion Batteries - Wen, Yunping; Chen, Long; Pang, Ying; Guo, Zhaowei; Bin, Duan; Wang, Yong-gang; Wang, Congxiao; Xia, Yongyao (ACS applied materials & interfaces, 2017)
This paper reports a facile sol–gel synthesis method to successfully prepare the TiP2O7 /expanded graphite (EG) nanocomposite as an advanced anode material for aqueous lithium-ion batteries. The constructed TiP2O7 nanocomposites (50–100 nm) are in situ encapsulated in the pore and layer structure of expanded graphite with good conductivity and high specific surface area. As a consequence, the resulting TiP2O7/EG electrode exhibits a reversible capacity of 66 mAh g–1 at 0.1 A g–1 with an appropriate potential of −0.6 V before hydrogen evolution in aqueous electrolytes, and also demonstrates greatly enhanced cycling stability with 75% capacity retention after 1000 cycles at the current density of 0.5 A g–1. A full cell consisting of TiP2O7/EG anode, LiMn2O4 cathode, and 1 M Li2SO4 electrolyte delivers a specific energy of 60 Wh kg–1 calculated on the weight of both cathode and anode materials with an operational voltage of 1.4 V. It also exhibits superior rate capability and remarkable cycling performance with a capacity maintenance of 66% over 500 cycles at 0.2 A g–1 and 61% at 1 A g–1 over 2000 cycles.